Adaptive Rate Allocation Technique for Mixed Traffic Users in Communication Network - Kumar, Neeraj; Awasthi, Shashank; Ahmad, Anwar (International Journal of Engineering and Technology, 2018)
In this paper, a network utility maximization based rate allocation technique is proposed for mixed traffic users. Each user is running a network application type of either elastic traffic or inelastic traffic. A utility function is defined for each elastic trafficand inelastic traffic behaving application. Network utility maximization approach maximizes utilities in given range of maximumthroughput rate constraint. Proposed technique adaptively allocates rate to users as increasing in range of maximum rate constraint.It proposes dynamic change in parameters of utility functions with respect to change in maximum rate constraint. Results of theproposed rate allocation technique is compared with existing techniques, which shows improved throughput rate for users at anyvalue of maximum rate constraint.
Keywords: Utility function; proportional fairness; price; demand; adaptive rate; allocation; throughput; logarithmic; sigmoidal.